Correlates of trail usage for physical activities in rural Appalachia, USA - Louisa A. SUMMERS; Ram LAKHAN; Peter H. HACKBERT (Journal of Health and Social Sciences)
Introduction: Physical inactivity is associated with several negative consequences. Trails in USA have been seen as useful part of build environment in facilitating physical activities for all people. Understanding of the role of sociodemographic and environmental aspects with trail usage can guide interventional plan for trails in Berea, USA. Purpose: This study aims to examine the correlates of trail usage for physical activities in rural Appalachia. Methods: It is a cross-sectional research design. Data for three years, 2017, 2018 and 2019 was collected. Parametric test including t-test was applied to observe differences in physical activities minutes per week for gender and analysis for variance for ethnicity, education, income, and overall health. Independent median test was used in observing difference with year and simple regression for age. Results: Physical activities on trails were found associated with education and overall health for winter (P < 0.05). Age was found associated with more physical activity per week during winter. Physical activities were not found different with gender, ethnicity, and income during summer and winter (P > 0.05) in the same year while comparing between three year from 2017 to 2019, physical activities per minute were found significantly different for both seasons (P < 0.05). Conclusion: Findings suggest that winter and age are positively associated with physical activities in Berea trails. Education and overall health also have impact on this behavior. Findings of this study may be very useful in developing promotional activities for younger people and summer time.